PENGARUH PELATIHAN, PENGAWASAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PLN (PERSERO) ULP BERASTAGI - Surbakti, Rut Piorida br; Sihombing, Sarimonang (UNIKA Santo Thomas, 2022)
This study aims to determine the effect of training, supervision and work discipline on employee performance at PT. PLN (Persero) ULP Berastagi. The population in this study were all employees of PT. PLN (Persero) ULP Berastagi, totaling 52 people. Given the small number of populations, the researchers used the entire population as a sample. The analytical technique used in this research is multiple linear regression. The coefficient of determination (R Square) of 0.652 means that variations in employee performance can be explained by variations in training, supervision and work discipline, by 65.2% and the remaining 34.8%, explained by other variables such as commitment, work spirit, motivation and others. The results of hypothesis testing simultaneously indicate that training, supervision and work discipline have a positive and significant effect on employee performance at PT. PLN (Persero) ULP Berastagi. This is indicated by the significance value of F, 0.000 < (0.05). Testing the hypothesis partially shows that training, supervision and work discipline have a positive and significant effect on employee performance at PT. PLN (Persero) ULP Berastagi. This is indicated by the significance value of each independent variable smaller than (0.05). PT. PLN (Persero) ULP Berastagi should pay more attention to the training materials provided to employees, improve supervision and evaluate work discipline so that performance can be improved.